2015
DOI: 10.1044/2015_aja-14-0058
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Methods for Measuring Listening Effort As Part of an Audiologic Test Battery

Abstract: Purpose To evaluate two measures of listening effort (a self-report measure and a word-recall measure) regarding their suitability for inclusion in a comprehensive audiologic testing protocol. The relationship between the two measures was explored and both measures were examined with regard to validity, sensitivity, and impact on speech intelligibility performance. Method Thirty adults with normal hearing participated. Speech intelligibility performance was evaluated at 4 SNRs using keywords embedded in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 29 publications
7
61
2
Order By: Relevance
“…Some might not accept the notion that people can accurately self-report listening effort in the laboratory or in the real world and might prefer to evaluate performance using a dual-task methodology. Johnson et al (2015) determined that the laboratory self-report method used for this study is equally valid, and in some conditions, preferred over a dual-task measure. The findings of the current study lend further support for the sensitivity and validity of the laboratory self-report measure of listening effort: the only statistical indication of better performance with premium-feature hearing aids was a rating of listening effort in the lab for one brand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some might not accept the notion that people can accurately self-report listening effort in the laboratory or in the real world and might prefer to evaluate performance using a dual-task methodology. Johnson et al (2015) determined that the laboratory self-report method used for this study is equally valid, and in some conditions, preferred over a dual-task measure. The findings of the current study lend further support for the sensitivity and validity of the laboratory self-report measure of listening effort: the only statistical indication of better performance with premium-feature hearing aids was a rating of listening effort in the lab for one brand.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we expected that the AFAAF materials and testing procedure would be appropriate for revealing reductions in listening effort that might result from the premium features. Prior to this study we compared the rating method, described below, with a dual-task measure (Johnson et al 2015). That study demonstrated that the rating method was more sensitive to changes in listening demand (i.e., changes in SNR and linguistic context) which were presumed to impact listening effort.…”
Section: Methodsmentioning
confidence: 99%
“…Even though there is interest among scientists and clinicians in determining the factors that underlie effortful listening, a challenge in this quest has been reaching a consensus about what is meant by listening effort and how to measure it (McGarrigle et al 2014; Johnson et al 2015). As summarized in the consensus paper (Pichora-Fuller et al, this issue, pp.…”
Section: Quantifying Effortful Listening: Clinical Relevancementioning
confidence: 99%
“…On the one hand, there are examples demonstrating perceived differences in listening effort across conditions that did not show relative performance differences (e.g. Rudner et al, 2012; Johnson et al, 2015; van den Tillaart-Haverkate et al, 2017), and Humes (1999) found the two variables to be separate hearing aid outcome measures. On the other hand, there are examples in which ratings of effort do follow recognition scores (e.g.…”
Section: Introductionmentioning
confidence: 99%